A Descriptive Comparison of the Epidemiological Characteristics of Delta and Omicron Variant-Driven Outbreaks in Bhutan - Sangay Rinchen; Tandin Zangpo; Sonam Wangchuk; Sithar Dorjee; Tandin Dorji; Ugyen Tshering; Jamyang Choden; Pema Yangzom; Deki Yangzom; Pempa Pempa; Laigdhen Dzed; Dechen Wangmo; et al. (Zoonotic Diseases)
SARS-CoV-2 rapidly mutated, causing different waves of outbreaks worldwide. Bhutan experienced three major outbreaks of COVID-19 before experiencing the outbreak driven by the Omicron variant in January 2022. The data collected by the National Outbreak Investigation and Surveillance Team during the Delta variant-driven outbreak and Omicron outbreak were accessed and analyzed. The data were analyzed using R statistical software. Descriptive analysis was carried out for the entire dataset and the statistical comparison between the two outbreaks was carried out using student’s t-test and Pearson’s chi-square test. During the Delta variant-driven outbreak, a total of 1648 cases were reported, with a daily average of 13 cases. The highest one-day case number reported was 99. On the contrary, within 33 days, a total of 3788 cases were reported with a daily average of 115 cases during the Omicron outbreak. The highest one-day case number reported was 312. The median incubation period was 3 days (range = 0–18 days) and 1 day (range = 0–14 days) during the Delta and Omicron-driven outbreaks, respectively. The number of symptomatic cases was significantly higher during the Delta outbreak (p-value < 0.0001). Of the total cases reported during the Delta outbreak, 1175 (71.3%) had received a single dose of the vaccine, 79 (5%) received two doses, while 394 (24%) were unvaccinated. During the Omicron outbreak, 1957 (52%) cases had received their booster (third dose), 904 (23.8%) received two doses and only 40 (1%) received a single dose of the vaccine. The number of unvaccinated cases was 887 (23.4%), of which 375 (10%) were children below 12 years. Our findings corroborate the enhanced transmissibility of the Omicron variant as reported elsewhere. We report significantly less symptomatic cases during the Omicron outbreak. Further, our data show that the incubation period for the Omicron variant is shorter compared to the Delta variant (p-value < 0.0001).